CONSIDERENTE METODICE PRIVIND EXPUNEREA PROCESULUI DE MODELARE - USM ADMIN (Moldova State University, 2010)
The methodical issues of treating the modeling process in the lyceum course of computer science are analysed. Some didactic solutions regarding the examined subjects are proposed.